Development of a Solid-state Laser for Metal Marking Equipment - Khoi, Giang Manh; Tien, Do Xuan; Chien, Trinh Dinh (VNU Journal of Science: Mathematics - Physics; Vol 33 No 2, 2017)
Abstract:   Laser radiation has many unique properties, such as highly focused, beam profile and selectable monochromatic wavelength, that suitable for many application in industry, biology technology as well as environmental processing. National Center for Laser Technology have developed the laser devices with application-oriented in the Industry is one of the key directions of us. With the active support of National Center for Technological Progress, we have successfully studied and mastered the technology to manufacture the laser equipments for industrial applications. In this report, we will introduce the technologies in the industrial laser equipments and the customers are trusting.